Spatial information on the Central Mindanao University’s Academic Services in the Northern Mindanao geographically isolated and disadvantaged areas - Bruno, Angela Grace Toledo; Bruno, Eric N.; Paquit, Joseph C. (2022)
Central Mindanao University (CMU) is a premier university in Northern Mindanao with a mission to provide quality education. In response to Sustainable Development Goal #4 on Quality Education and the government's program on Geographically Isolated and Disadvantaged Areas (GIDAs), this study aims to assess the extent of CMU in providing academic services, particularly in GIDAs in Northern Mindanao, Philippines. This study employed an online survey among CMU students and alumni supplemented with secondary data. The study applied the Geographic Information System (GIS) to generate maps and spatially analyze the data. A total of 721 students and 641 alumni responded through the online survey, with 3,594 alumni sourced out from CMU graduation programs. The study's findings revealed that the distribution of students and alumni in CMU is mostly in Bukidnon, particularly in the central and southern parts. Most of the students and alumni in Northern Mindanao are spread in non-GIDAs, although a considerable percentage is in GIDAs. For CMU to respond to GIDAs and SDG Goal #4, the University should craft scholarship programs to attract students and extend its academic services in GIDAs to provide quality education in Northern Mindanao significantly.
Keywords: Educational quality; Central Mindanao University